The response of root-zone soil bacterial community, metabolites, and soil properties of Sanyeqing medicinal plant varieties to anthracnose disease in reclaimed land, China - Xuqing Li; Qiujun Lu; Rahila Hafeez; Solabomi Olaitan Ogunyemi; Ezzeldin Ibrahim; Xiaoxu Ren; Zhongling Tian; Songlin Ruan; Mohamed Mohany; Salim S. Al-Rejaie; Bin Li; Jianli Yan (Heliyon, 2024)
Objectives: To enhance the utilization of reclaimed land, Sanyeqing (SYQ) has been extensively cultivated in Zhejiang province, China. However, the prevalence of anthracnose has significantly hindered SYQ growth, emerging as a primary obstacle to its production. This study aimed to elucidate SYQ's responses to anthracnose in reclaimed land environments by comprehensively analyzing root-zone bacterial community structure, metabolites, and soil properties. Methods: The experiment was conducted on reclaimed land in Chun'an, China. In order to evaluate the responses of SYQ to anthracnose, the fresh and dry weight of SYQ tubes, the soil properties, the high-throughput sequencing, and metabolomics assay were carried out. Results: Significant differences were observed between an anthracnose-resistant variety (A201714) and an anthracnose-susceptibile variety (B201301). Fresh and dry weight increased 131.53 % and 144.82 % for A201714 compared to B201301.Lacibacterium (39.85 %), Gp6 (21.83 %), Gp5 (21.49 %), and Sphingomonas (18.84 %) were more prevalent, whereas Gp3 (22.71 %), WPS-1 (18.88 %), Gp4 (15.60 %), Subdivision3 (14.70 %), Chryseolinea (14.37 %), and Nitrospira (0.76 %) were less prevalent in A201714 than B201301. A total of 24 bacterial biomarkers were detected in all soil samples, while the network suggests a more stable soil bacterial community in A201714 than in B201301. Eight differentially expressed metabolites (DEMs) that belonged to lipids and lipid-like molecules, organic acids and derivatives, benzenoids, nucleosides, nucleotides, and analogues were found between two soil samples, and all these eight DEMs were downregulated in A201714 and had a strong correlation with 12 genera of bacteria. Moreover, the data from the redundancy analysis indicated that the main variables affecting changes in the bacterial communities were pH, available phosphorus (AP), available potassium (AK), microbial biomass carbon (MBC), and microbial biomass nitrogen (MBN). Conclusion: This research offers new insights into the SYQ response to anthracnose in reclaimed land and provides valuable recommendations for the high-quality SYQ cultivation and production.